2003
DOI: 10.1029/2003gl017903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the solar wind electric field and ionospheric conductance on the cross polar cap potential: Results of global MHD modeling

Abstract: The behavior of the cross polar cap potential, ΦPC, under strong solar wind conditions is studied using global MHD simulations. Simulations using two typical values of the ionospheric Pedersen conductance in agreement with others show that the cross polar cap potential is reduced compared to the corresponding potential in the solar wind due to the stagnation of the magnetosheath flow and the existence of parallel potentials. However, it is the ionospheric conductance that affects the value of ΦPC the most: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 9 publications
7
88
1
Order By: Relevance
“…These clusters of plots show three different ways in which saturation of the ionospheric CPCP has typically been shown: (1) the time series plots show that the Boyle et al (1997) estimation of the CPCP typically becomes larger than the AMIE CPCP when the IMF B z component becomes large and negative; (2) the upper scatter plot shows that the Boyle et al (1997) estimated CPCP is linear for large REFs, while the AMIE CPCP is significantly lower than this linear estimate; and (3) when the Boyle et al (1997) In most previous studies of the saturation of the cross polar cap potential (e.g. Russell et al, 2001;Merkine et al, 2003;Nagatsuma, 2002), they show plots such as Figs. 1-4, implying a relationship between an electric field and a potential.…”
Section: Resultsmentioning
confidence: 99%
“…These clusters of plots show three different ways in which saturation of the ionospheric CPCP has typically been shown: (1) the time series plots show that the Boyle et al (1997) estimation of the CPCP typically becomes larger than the AMIE CPCP when the IMF B z component becomes large and negative; (2) the upper scatter plot shows that the Boyle et al (1997) estimated CPCP is linear for large REFs, while the AMIE CPCP is significantly lower than this linear estimate; and (3) when the Boyle et al (1997) In most previous studies of the saturation of the cross polar cap potential (e.g. Russell et al, 2001;Merkine et al, 2003;Nagatsuma, 2002), they show plots such as Figs. 1-4, implying a relationship between an electric field and a potential.…”
Section: Resultsmentioning
confidence: 99%
“…This measured progression supports the finite grid-resolution underestimate picture. Note that other simulations see this difference between the magnetosphere and ionosphere [e.g., Merkine et al, 2003]. And note further that arguments have been made that there is a difference in potentials across the real ionosphere and real magnetosphere [Russell et al, 2001].…”
Section: à3mentioning
confidence: 99%
“…Some of the global MHD simulations in the literature have also explored polar cap saturation in this modestly driven regime [e.g., Fedder and Lyon, 1987;Siscoe et al, 2002a;Ridley et al, 2004]. Other simulations have explored polar cap saturation with very strong driving [e.g., Raeder et al, 2001;Merkin et al, 2005b;Raeder and Lu, 2005;Ridley et al, 2006] or have varied their solar wind parameters into the very strongly driven regime [e.g., Siscoe et al, 2002b;Merkine et al, 2003;Merkin et al, 2005a;Ridley, 2007;Lavraud and Borovsky, 2008].…”
mentioning
confidence: 99%
“…As a matter of fact, it was used to study the dependence of the MR voltage and transpolar potential on the solar wind electric field and ionospheric Pedersen conductance [4,5,13,14] and the paths of the FACs [12,15,16]. In particular, Guo et al [16] found that more than 50% of the region 1 FAC may come from the bow shock under strong southward IMF conditions.…”
mentioning
confidence: 99%
“…Note that here the ionosphere is not only a passive load for the M-I system, but plays a crucial role in the M-I coupling. It directly affects the transpolar potential and the FAC intensity, and exerts an indirect but important influence on the magnetosphere configuration, the magnetosheath flow, and the MR voltage [13,14]. Hence the effect of the ionospheric conductance must be included while studying the SW-M-I coupling.…”
mentioning
confidence: 99%